An unusual case of hematemesis and epistaxis caused by a pheochromocytoma - Ugur, Kader; Girgin, Mustafa; Bahcecioglu, Ibrahim Halil; Artas, Hakan; Simsek, Fikri Selcuk; Aydin, Suleyman (Sage Publications Ltd, 2018)
Pheochromocytoma is a rare catecholamine-secreting neoplasm that is the cause of hypertension in <0.2% of patients with hypertension. We encountered an unusual case of pheochromocytoma involving hematemesis and epistaxis episodes with accompanying hypertensive attacks. Venous ectasia was detected in the esophagus. Abdominal magnetic resonance imaging revealed an adenoma in the left adrenal region. The present case illustrates that pheochromocytoma can mimic different clinical conditions.
Keywords: Pheochromocytoma; hematemesis; epistaxis episodes; hypertension; venous ectasia; magnetic resonance imaging